Pemodelan hubungan antara kesejahteraan hidup, keserakanan hidup, keserakanan dan kesejahteraan di tempat kerja dengan efikasi guru secara efikasi guru secara kolektif - Yusof, Yusni Zaini (Universiti Utara Malaysia Press, 2015)
Purpose – Based on a social cognitive model, the study examined direct and indirect precursors of collective teacher efficacy.Specifically, it assessed the roles of personal well-being, collegiality and workplace well-being to explain collective teacher efficacy.Methodology – A sample of 836 teachers were randomly selected from twelve MRSM in the east coast of Malaysia. Data were obtained through a survey questionnaire that comprised 85 items and analysed using descriptive statistics and Structural Equation Modelling. Findings – Results indicate that personal well being, collegiality and workplace well-being significantly influence collective teacher efficacy. Based on the holistic approach in model evaluation, the overall measurement model and the structural model are found to be adequately fit. The findings of the structural equation modelling indicate that workplace well-being partially mediates the relationship of personal well-being, collegiality and collective teacher efficacy. Compared to personal well-being, teacher collegiality seems to exhibit a stronger impact on collective teacher efficacy.Significance – The study proposes a model which highlights the importance of personal well-being, collegiality and work-place well-being as significant contributors to collective teacher efficacy. It also identifies the importance of teacher collegiality in developing collective teacher efficacy.